2014
DOI: 10.1103/physrevstab.17.110705
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent wave front propagation simulation of a hard x-ray split-and-delay unit: Towards a measurement of the temporal coherence properties of x-ray free electron lasers

Abstract: For the European x-ray free electron laser (XFEL) a split-and-delay unit based on geometrical wavefront beam splitting and multilayer mirrors is built which covers the range of photon energies from 5 keV up to 20 keV. Maximum delays between Δτ=±2.5ps at hν=20keV and up to Δτ=±23ps at hν=5keV will be possible. Time-dependent wave-optics simulations have been performed by means of Synchrotron Radiation Workshop software for XFEL pulses at hν=5keV. The XFEL radiation was simulated using results of time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…20,21 Past experience has shown that a careful characterization and calibration of slope measuring profilers is essential to achieve the accuracy requirements for the synchrotron optics of today. [22][23][24] The spatial resolution achievable by slope measuring deflectometry is of special importance, mainly in the case when topography data are used to simulate the performance of optical components 25,26 or when deterministic surface finishing is applied to remove residual figure deviations. [27][28][29] For such use, a precise spatial frequency calibration is essential.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Past experience has shown that a careful characterization and calibration of slope measuring profilers is essential to achieve the accuracy requirements for the synchrotron optics of today. [22][23][24] The spatial resolution achievable by slope measuring deflectometry is of special importance, mainly in the case when topography data are used to simulate the performance of optical components 25,26 or when deterministic surface finishing is applied to remove residual figure deviations. [27][28][29] For such use, a precise spatial frequency calibration is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The delay time is determined by the path length difference between the delay branches, resulting in a jitter-free delay time control through precise adjustments of the path length difference. In the hard X-ray regime, several SDO layouts based on grazing-incidence multilayer mirrors (Roling et al, 2014), diffraction gratings (David et al, 2015) and perfect crystals (Roseker et al, 2009(Roseker et al, , 2011Stetsko et al, 2013;Sakamoto et al, 2017) have been proposed, and some systems have been tested at synchrotron and/or XFEL facilities. In particular, crystal-based SDO systems can easily generate a large delay time of more than 100 ps with a reasonably small apparatus, because of a large deflection angle (greater than several degrees) for Bragg diffractions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of an experimentally measured mirror profile is always the best solution and data from existing mirrors (or simulated or modified from the real measurements) can be used for predicting performances of beamlines under design. This approach has been used in the literature (Roling et al, 2014;Siewert et al, 2010;Yashchuk et al, 2015a) using data from mirrors that have been measured in the facility, or have been provided by the manufacturer. But in the general case the accessibility of good experimental data of state-of-the-art mirrors for simulations of new beamlines is difficult, because these data usually live in the computers of the metrology facilities and usually only their SD values of slopes and heights and perhaps some graphics are available, which cannot be directly used for the simulations.…”
Section: Introductionmentioning
confidence: 99%